Struktur Komunitas Makrozoobentos di Perairan Padang lamun desa wisata Gili Gede, Sekotong, Lombok Barat - Febiliyadi, Aqidatul; Hilyana, Sitti; Astriana, Baiq Hilda (Jurnal Ilmu Kelautan Lesser Sunda, 2023)
Gili Gede is an island in Lombok. Macrozobenthos are bottom-dwelling animals that play an important role and are often used as bioindicators to assess the quality of aquatic ecosystems. This study provides important basic data for determining water quality based on the diversity of macrobenths from Gili Gede waters. This research was conducted in October 2022. Samples for this study were obtained from 9 predetermined points on 3 transect lines. Then it is calculated using the diversity, uniformity, and dominance formulas of Shannon-Wiener and the sediment analysis formula. Based on the results of the assistance, there were 34 macrozoobenthos species, a total of 275 individuals. the diversity index value in these waters is 2.18 which is in the medium category. The uniformity index has a value of 0.62 which is included in moderate uniformity. The Dominance Index is 0.29 which is low. Most of these aquatic substrates have sedimentary characteristics, namely dusty clay. The diversity of macrozoobenthos in these waters is 2.18, included in the medium diversity category (H') 1<H<3, indicating that these waters have sufficient productivity stability. balanced ecosystem conditions, balanced ecological pressures, and water quality considered suitable for the growth and development of macrozoobenthos.